Mobility of screw dislocation in BCC tungsten at high temperature in presence of carbon. (1st January 2022) - Hachet, Guillaume; Caillard, Daniel; Ventelon, Lisa; Clouet, Emmanuel
Graphical abstract: Abstract: The interplay of screw dislocations with carbon atoms is investigated in tungsten at high temperature using in situ straining experiments in a transmission electron microscope (TEM) and through ab initio calculations. When the temperature is high enough to activate carbon diffusion, above 1373 K, carbon segregates in the core of screw dislocations and modifies their mobility, even for a carbon concentration as low as 1 appm. TEM observations reveal the reappearance of a Peierls mechanism at these high temperatures, with screw dislocations gliding viscously through nucleation and propagation of kink-pairs. The mobility of screw dislocations saturated with carbon atoms is then investigated with ab initio calculations to determine kink-pair formation, nucleation and migration energies. These energies are used in kinetic Monte-Carlo simulations and in an analytical model to obtain the velocity of screw dislocations as a function of the temperature, the applied stress and the dislocation length. The obtained mobility law parametrised on ab initio calculations compares well with experiments.